Heat Pump Drying of Arabica Coffee Beans: Influence of Inlet Air Conditions on Drying Rate Constant - Hanifah, Muhamad Abu; Kosasih, Engkos Achmad; Fauzi, Muhammad Burhanuddin (Jurnal Konversi Energi dan Manufaktur, 2025)
Drying is a crucial step in agricultural processing as it reduces moisture content, extends shelf life, and preserves product quality. For heat-sensitive Arabica coffee beans, heat pump drying (HPD) is an efficient and energy-saving method. This study investigates the drying characteristics of wet Arabica coffee beans using an HPD system, focusing on determining the drying rate constant (k) at various inlet air temperatures and humidity conditions. The drying process was conducted for 30 minutes at a constant air mass flux rate of 0.69 kg/m²-s at temperatures of 45, 50, 55, 60, and 65°C. Inlet air conditions were controlled with a cooling system at 10, 15, and 20°C, compared to ambient air without cooling. The results showed that increasing drying temperature and decreasing inlet air humidity significantly enhanced the drying rate. Additionally, the study explored the relationship between the constant air mass flux and variable parameters, including air temperature and humidity, which directly affected the drying rate constant (k). The highest k value (17.66 × 10⁻⁵ s⁻¹) was observed at 65°C with air from the cooling system at 10°C, indicating that combining high temperature and dry air improves drying efficiency.